First 3D modelling of tungsten erosion and migration in WEST discharges adopting a toroidally non-symmetric wall geometry. (March 2023) - Di Genova, S.; Ciraolo, G.; Gallo, A.; Romazanov, J.; Fedorczak, N.; Bufferand, H.; Tamain, P.; Rivals, N.; Marandet, Y.; Brezinsek, S.; Serre, E.
Abstract: Numerical analysis is a useful tool to investigate tungsten (W) sources and transport across plasma in W Environment Steady state Tokamak (WEST) plasma discharges, as it highlights physical mechanisms not always directly observable in experiments. Modelling activities were performed to study W erosion from WEST plasma-facing components (PFCs), as well as W migration through the plasma. For the first time, it was adopted a toroidally asymmetric wall geometry consisting of toroidally localized objects representing WEST antennas. To simulate WEST boundary plasma, 3D non-axisymmetric SOLEDGE transport simulations were performed with simplifying assumptions (pure deuterium plasma, a fluid model for neutrals). Results were then used as background for ERO2.0 runs to model W migration. On the sides of the toroidally localized objects, two thin stripes modelled WEST W antenna protections. Simulations suggest that particles eroded from the antennas protections may dominate the core W contamination in the analysed wall configuration. The findings suggest that these 3D non-axisymmetric models may be needed on a broader range of plasma conditions and wall configurations to accurately model the W migration in WEST. Highlights: 3D Modelling of WEST tokamak boundary plasma. Study plasma interaction with a toroidal non-axisymmetric wall. Analysis of plasma migration across plasma. Modelling of limiters as toroidally localized objects. Examination of the effects of limiters on tungsten core contamination.